Enhancing structural diversity of terpenoids by multisubstrate terpene synthases - Li, Min; Tao, Hui (Beilstein Journal of Organic Chemistry, 2024)
Terpenoids are one of the largest class of natural products with diverse structures and activities. This enormous diversity is embedded in enzymes called terpene synthases (TSs), which generate diverse terpene skeletons via sophisticated cyclization cascades. In addition to the many highly selective TSs, there are many promiscuous TSs that accept multiple prenyl substrates, or even noncanonical ones, with 6, 7, 8, 11, and 16 carbon atoms, synthesized via chemical approaches, C-methyltransferases, or engineered lepidopteran mevalonate pathways. The substrate promiscuity of TSs not only expands the structural diversity of terpenes but also highlights their potential for the discovery of novel terpenoids via combinatorial biosynthesis. In this review, we focus on the current knowledge on multisubstrate terpene synthases (MSTSs) and highlight their potential applications.
Keywords: noncanonical terpene; substrate promiscuity; synthetic biology; terpene synthase; terpenoid